Social media influence on Malay family resilience towards challenges of the internet - Saodah Wok,; Junaidah Hashim,; Kalthom Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2016)
In this modern and technological era, the social media can become a threat to the family. This study applies the Dependency Theory for users who actively seeking information at the expense of their own family resilience towards challenges of the Internet. As such, this study tries to explore the differences between the social media influence on the rural and urban Malay families. The objectives of the study are (1) to compare the social media used for communicating with family members and friends between the rural and urban families; (2) to compare the influence of social media on the rural and urban families; and (3) to differentiate the influence of social media on the rural and urban families on family resilience towards challenges of the Internet. A total of 800 respondents, representing families were surveyed, using the questionnaire for data collection. The results indicate a marked digital divide between the rural and urban families where the rural families use it for e-commerce while the urban families use more of the Internet for chatting, reading online newspaper and other materials while. The rural families use fewer types of the social media than the urban families. The social media influence the rural families positively while the urban families are affected both positively and negatively. As a whole, the rural families are more resilient than the urban families. Nonetheless, the Dependency Theory holds true for the social media influence on individualistic and antagonistic urban families.